Mechanical properties and metallurgical characterization of AA6082-T6 alloy welded by refill friction stir spot welding - Silva, Bruno Hessel (2019)
The efforts to produce automobiles with intense use of aluminum alloys is growing and the 6XXX series of aluminum alloys are important for this scenario. However, the current joining technologies applied in these alloys present limitations regarding weld uniformity, energy input and production costs. Refill Friction Stir Spot Welding (RFSSW) is a solid-state welding technique with potential to surpass these limitations. In order to validate this technique in automotive applications, issues must be addressed such as obtaining mechanical properties standards; determining the effect of process parameters on weld structure and properties; optimizing cost-efficiency factors and others. In this work the application of RFSSW in the AA6082-T6 alloy was studied focusing on: (i) the effect of process parameters on weld structure and mechanical properties; (ii) understanding of fracture behavior of the welds under static and cyclic load; and (iii) the influence of Bake Hardening treatment on the weld structure and properties. Optimized process parameters set with suitable welding time for industry applications were obtained using statistical analysis maximizing static mechanical properties. Macro/microstructural analysis were carried out and demonstrated that the Plunge Depth parameter has the most relevant influence on weld strength and fracture behavior due to its effect in hook shape formation, which is an intrinsic feature in RFSSW welds. Hardness and thermal characterization helped to understand the effect of Bake Hardening on reprecipitation and overaging process in different weld regions and, consequently, on the mechanical properties and fracture behavior of the welds. Using Weibull Statistical analysis, L-N fatigue curves were obtained and demonstrated that, regardless the hook shape, the curves presented similar trend and fatigue limit close to 12% of the maximum Shear Load. Finally, based on fatigue fracture surface characterization, it was found that the hook shape configuration has a relevant effect on fracture behavior only for low-cycle load conditions.